2017
DOI: 10.1021/acs.jafc.6b05192
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Wheat Endoplasmic Reticulum Oxidoreductin 1 Improved Wheat Dough Properties and Bread Quality

Abstract: Recombinant wheat endoplasmic reticulum oxidoreductin 1 (wEro1) with considerable ability was expressed in Escherichia coli. The functional roles of wEro1 in flour processing quality were investigated by farinographic, rheological, texture profile analysis, electrophoresis, size exclusion chromatography, scanning electron microscopy, and Fourier transform infrared spectroscopy. wEro1 exhibited an obvious oxidation activity of sulfhydryl groups in small molecule and protein. Addition of wEro1 could strengthen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…It is believed that PDI is the physiological substrate of mammalian Ero1, and the oxidation of PDI is mainly under the assistance of Ero1 [69]. However, the oxidation of plant PDI may also require the assistance of plant Ero1 [70,71].…”
Section: Oxidoreductase Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that PDI is the physiological substrate of mammalian Ero1, and the oxidation of PDI is mainly under the assistance of Ero1 [69]. However, the oxidation of plant PDI may also require the assistance of plant Ero1 [70,71].…”
Section: Oxidoreductase Activitymentioning
confidence: 99%
“…In another study, recombinant wheat Ero1 (wEro1) was expressed and purified in Escherichia coli, and the wEro1 was added to wheat dough. By analyzing the rheological properties of the dough, such as viscoelasticity, it was found that wEro1 may promote the cross-linking of disulfide bonds, leading to the formation of gluten polymers [70]. They further investigated the properties of recombinant wEro1 containing FAD cofactor and its influence on Chinese steamed bread qualities.…”
Section: Proposed Catalytic Mechanism Of Wpdimentioning
confidence: 99%
See 1 more Smart Citation
“…This result implies that acid hydrolysis generally leads to a more elastic gluten system. An increase in G 0 and a decrease in tand indicated that the quality of the gluten had improved because increased elasticity prevents gas cell breakage during fermentation (Liu et al 2017)…”
Section: Dynamic Oscillatory Testsmentioning
confidence: 99%
“…Previous research showed that wheat endoplasmic-reticulum oxidoreductin 1 (wEro1), glucose oxidase, and pyranose oxidase could enhance mixing characteristics and viscoelastic properties of dough. 8,11 It was reported that wheat glutaredoxin together with wheat thioredoxin has a positive effect on flour and dough properties and bread making. 12 Catalase (EC 1.11.1.6), which catalyzes the decomposition of hydrogen peroxide, mostly exists in aerobic living organisms to protect the cells from oxidative stress triggered by overproduced hydrogen peroxide.…”
Section: ■ Introductionmentioning
confidence: 99%